Emisión Y Transmisión De Comprobantes Electrónicos Extemporáneos Y Su Repercusión En El Manejo Económico De La Empresa Comercial Muñoz, Cantón Quevedo, Año 2023 - Cruzatty Domínguez, Víctor Hugo (2025)
This research, entitled "Issuance and transmission of late electronic receipts and their impact on the financial management of Comercial Muñoz, Quevedo Canton, 2023," had the main objective of evaluating the incidence of the issuance and transmission of late electronic receipts and their impact on the company's financial management. A mixed approach was used, combining inductive, deductive, historical, and descriptive methods, with the aim of identifying the causes and effects of the problem and thus obtaining general conclusions from the research. The study population consisted of 121 people; therefore, since it is finite, the sampling was census-based, meaning the entire study population was covered. A pre-prepared interview was conducted with the billing manager and surveys were conducted with the company's clients. Among the most notable results, it was evident that the late issuance of electronic receipts has a negative impact on Comercial Muñoz's credibility with the IRS, customers, and suppliers. Failure to comply with regulations can result in tax penalties and a loss of trust in the company. The conclusion is that the late issuance and transmission of electronic receipts has a direct impact on Comercial Muñoz's regulatory compliance, credibility, and financial management.